2019
DOI: 10.1590/s0102-865020190060000001
|View full text |Cite
|
Sign up to set email alerts
|

Bioceramic cement in the filling of bone defects in rats

Abstract: To evaluate PBS ® MCIMMO cement in the filling of bone defects. Methods: Thirty-six adult male Wistar rats were divided into three groups of twelve individuals each (group 1, group 2 and group 3). In all groups, a bone failure in the femur was induced, 2.0 mm wide and 7.0 mm deep. In group 1, the PBS ® MCIMMO cement was applied to the bone defect produced and a titanium implant (CONNECTION ®) 1.5 mm thick and 6 mm long was installed. In group 2, only the PBS ® CIMMO cement was installed. In group 3, only bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…However, ALP activity was high in this cement group after 5 days of exposure. PBS-HP has a short setting time due to the pozzolan in its composition 15 , which probably leads to the bioavailability of Ca 2+ in a time-dependent manner that interferes with the material’s potential to induce osteogenesis 9 , 10 . The results of our study, especially the osteogenic marker expression pattern and ALP activity, indicated an intermediate to advanced phase of osteoblastic differentiation in the NeoMTA-P, ProRoot, Bio-C, MTA-HP, and PBS-HP groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ALP activity was high in this cement group after 5 days of exposure. PBS-HP has a short setting time due to the pozzolan in its composition 15 , which probably leads to the bioavailability of Ca 2+ in a time-dependent manner that interferes with the material’s potential to induce osteogenesis 9 , 10 . The results of our study, especially the osteogenic marker expression pattern and ALP activity, indicated an intermediate to advanced phase of osteoblastic differentiation in the NeoMTA-P, ProRoot, Bio-C, MTA-HP, and PBS-HP groups.…”
Section: Discussionmentioning
confidence: 99%
“…PBS HP, composed of dicalcium silicate, mineral oxides, and pozzolan, is a recently proposed cement. PBS HP showed promising results as a graft material in dental implants by maintaining the socket architecture 15 . Histological images showed newly formed fibroblasts, osteoid cells, mineralized bone tissue, and connective tissue encasing PBS HP.…”
Section: Introductionmentioning
confidence: 98%
“…Por fim, o cimento PBS HD® Cimmo (MJS Indústria e Comércio de Materiais para Saúde Ltda, Pouso Alegre, MG, Brasil) é um cimento Portland biocompatível e bioativo que contém aditivos naturais como pozzolana e carbonato de cálcio que conferem propriedades mecânicas como resistência à compressão 10,11 bem como o tempo de endurecimento 11 . Sua formulação não contém agentes radiopacificadores 10,11 .…”
Section: Resultsunclassified
“…Restoration of critical bone defects requires a sequence of processes, thus mainly depending on the integrity and biomechanical features of bone [ 1 , 2 ]. The most commonly used surgical procedure is bone grafting, to augment bone regeneration in orthopaedic surgery [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%